The bacterial pathogen Listeria monocytogenes and the interferon family: type I, type II and type III interferons - Dussurget, Olivier; Bierne, Hélène; Cossart, Pascale (Frontiers in Cellular and Infection Microbiology, 2014)
Interferons (IFNs) are secreted proteins of the cytokine family that regulate innate and adaptive immune responses to infection. Although the importance of IFNs in the antiviral response has long been appreciated, their role in bacterial infections is more complex and is currently a major focus of investigation. This review summarizes our current knowledge of the role of these cytokines in host defense against the bacterial pathogen Listeria monocytogenes and highlights recent discoveries on the molecular mechanisms evolved by this intracellular bacterium to subvert IFN responses.